The effects of e-Sports on physical and psychosomatic parameters: non-randomized controlled trials - Unuz, Halide; Kirmizigil, Berkiye (Edizioni Minerva Medica, 2025)
BACKGROUND: e-Sport is taking firm steps towards becoming the most popular sports field in the world with an increasing number of players and spectators. However, its popularity comes with negativity due to the physical and emotional stresses e-Sport create. Therefore, the study aims to investigate the effect of e-Sports on psychosomatic and physical parameters and to compare it with the control group. METHODS: Within physical factors, pain and fatigue levels were assessed with Visual Analog Scale (VAS), presence of musculoskeletal pain was evaluated with Expanded Nordic Musculoskeletal Questionnaire (NMQ-E). International Physical Activity Short Form (IPAQ-SF) was used to assess physical activity and posture was examined with New York Posture Rating Scale (NYPRS) and Craniovertebral Angle (CVA) method. For psychosomatic factors, Depression Anxiety and Stress Scale 21 (DASS 21) was used to assess mental status and Pittsburgh Sleep Quality Index (PSQI) was used to evaluate sleep quality. RESULTS: A highly significant difference was found in pain status in activity, sleep quality and posture analyzes of the groups (P50.01). Statistically significant differences were found in CVA, resting pain and fatigue levels, depression, anxiety, stress and physical activity values (P<0.05). Additionally in ENMQ, a statistically significant difference was found between groups in neck, hand and low back regions (P<0.05), but no significant differences were found in other body regions (P>0.05). CONCLUSIONS: Individuals who engage in digital gaming experience heightened levels of physical and psychosomatic stress. (Cite this article as: Unuz H, Kirmizigil B. The effects of e-Sports on physical and psychosomatic parameters: non-randomized controlled trials. J Sports Med Phys Fitness 2025 Jul 15. DOI: 10.23736/S0022-4707.25.16592-4)
Keywords: Musculoskeletal system; Pain; Depression